Donor preconditioning after the onset of brain death with dopamine derivate n-octanoyl dopamine improves early posttransplant graft function in the rat - Li, Shiliang; Korkmaz-İçöz, Sevil; Ruppert, Mihály; Loganathan, Sivakkanan; Hegedűs, Péter; Höger, Simone; Brune, Maik; Lasitschka, Felix; Karck, Matthias; Yard, Benito A.; Szabó, Gábor (American journal of transplantation, 2017)
Heart transplantation is the therapy of choice for end-stage heart failure. However, hemodynamic instability, which has been demonstrated in brain-dead donors (BDD), could also affect the posttransplant graft function. We tested the hypothesis that treatment of the BDD with the dopamine derivate n-octanoyl-dopamine (NOD) improves donor cardiac and graft function after transplantation. Donor rats were given a continuous intravenous infusion of either NOD (0.882 mg/kg/h, BDD+NOD, n = 6) or a physiological saline vehicle (BDD, n = 9) for 5 h after the induction of brain death by inflation of a subdural balloon catheter. Controls were sham-operated (n = 9). In BDD, decreased left-ventricular contractility (ejection fraction; maximum rate of rise of left-ventricular pressure; preload recruitable stroke work), relaxation (maximum rate of fall of left-ventricular pressure; Tau), and increased end-diastolic stiffness were significantly improved after the NOD treatment. Following the transplantation, the NOD-treatment of BDD improved impaired systolic function and ventricular relaxation. Additionally, after transplantation increased interleukin-6, tumor necrosis factor TNF-α, NF-kappaB-p65, and nuclear factor (NF)-kappaB-p105 gene expression, and increased caspase-3, TNF-α and NF-kappaB protein expression could be significantly downregulated by the NOD treatment compared to BDD. BDD postconditioning with NOD through downregulation of the pro-apoptotic factor caspase-3, pro-inflammatory cytokines, and NF-kappaB may protect the heart against the myocardial injuries associated with brain death and ischemia/reperfusion.
Gesehen am 20.07.2018
First published: 24 January 2017